(untitled) (Journal of Pharmaceutical Negative Results, 2023)
The infection caused by the bacteria Mycobacterium TB continues to be a major contributor to death rates around the globe. Antibiotic resistance is on the rise, and drug-resistant bacteria pose a serious danger to human health; thus, studying the causes of antibiotic tolerance is important. The lack of verified targets that allow for the elimination of chronic infections is a key barrier to the creation of new anti-tuberculosis medications. The physiological state that is regarded to be a key contributor to latent TB infection and the prolonged duration of tuberculosis therapy is one that is induced by the stringent response, which decreases replication and reduces the metabolic state under stressful situations. RelMtb is an enzyme that controls the buildup of (p)ppGpp, an effector molecule in the stringent response. Potentially useful insights into antibiotic tolerance and immune evasion, as well as novel approaches to treating TB, may result from learning to regulate this enzyme, which is thought to enable manipulation of the M. tuberculosis stringent response. The goal of this research is to get a better understanding of this route and to determine whether or not (p)ppGpp buildup is necessary to trigger the severe response. Using a combination of molecular cloning and genetic engineering, we have created a RelMtb over expression strain that is conditional but lacks the capacity to hydrolyze (p)ppGpp. Gene expression of interest is induced in this strain using an anhydrotetracycline inducing agent. Although genetic and protein evidence for inducible expression has been shown, further information is required to describe this strain and identify its true effects on (p)ppGpp and the stringent response. These results show that the aspartate route in Mtb is regulated by many metabolic pathways, plays an important role in Mtb persistence, and is a potential therapeutic target for TB treatment.